Induction of labour: Experiences of care and decision-making of women and clinicians. Issue 1 (February 2020) - Coates, Dominiek; Goodfellow, Alison; Sinclair, Lynn
Abstract: Background: There has been a rise in induction of labour over recent decades. There is some tension in the literature in relation to when induction is warranted and when not, with variability between guidelines and practice. Given these tensions, the importance of shared decision-making between clinicians and women is increasingly highlighted as paramount, but it remains unclear to what extent this occurs in routine care. Method: Using a scoping review methodology, quantitative and qualitative evidence were considered to answer the research question "What are the views, preferences and experiences of women and clinicians in relation to induction of labour more broadly, and practices of decision-making specifically?" To identify studies, the databases PubMed, Maternity and Infant Care, CINAHL and EMBASE were searched from 2008 to 2018, and reference lists of included studies were examined. Findings: 20 papers met inclusion criteria, in relation to (a) women's preferences, experiences and satisfaction with IOL; (b) women's experience of shared-decision making in relation to induction; (c) interventions that improve shared decision-making and (d) factors that influence decision-making from the perspective of clinicians. Synthesis of the included studies indicates that decision-making in relation to induction of labour is largely informed by medical considerations. Women are not routinely engaged in the decision making process with expectations and preferences largely unmet. Conclusion: There is a need to develop strategies such as decision aids, the redesign of antenatal classes, and clinician communication training to improve the quality of information available to women and their capacity for informed decision-making.